Association of Gc-globulin variation with susceptibility to COPD and diffuse panbronchiolitis - Ishii, T; Keicho, N; Teramoto, S; Azuma, A; Kudoh, S; Fukuchi, Y; Ouchi, Y; Matsuse, T (The European respiratory journal, 2001)
Chronic obstructive pulmonary disease (COPD) and diffuse panbronchiolitis (DPB) are both characterized by chronic airflow limitation. Although the aetiology of these diseases is under investigation, it is commonly hypothesized that neutrophils have a major role in the disease pathogenesis. The variation of the genes related to chemotaxis of neutrophils may confer a risk for the development of both COPD and DPB. In the present report, the authors investigated the association between genetic variation that codes for the 416th and 420th amino acid of Gc-globulin, reported to be associated with chemotaxis of neutrophils, and susceptibility to COPD and DPB. Blood samples obtained from patients with COPD (n=63), DPB (n=82), and-control subjects (n=82) were used for the genotyping assay. The proportion of GC*1F homozygotes was significantly higher in the COPD patients than the control subjects (COPD 36.5% versus control 20.7%), and the odds ratio for GC*IF homozygotes was 2.2 (95%, confidence interval 1.1-4.6) for the COPD group. There was no difference on the distribution of the other genotypes (GC*1F-1S heterozygotes, GC*1S homozvgotes, GC*2-1F heterozygotes, GC*2-1S heterozygotes and GC*2 homozygotes) or the allele frequencies among these groups. These findings suggest that the GC*IF gene polymorphism of Gc-globulin may be one of the risk factors for chronic obstructive pulmonary disease. However, no association between this polymorphism of Gc-globulin and susceptibility to diffuse panbronchiolitis was found.